1925
DOI: 10.1017/s002185960000558x
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the vapour pressure and water content of soils

Abstract: Much of the modern work on the physical properties of soil has been interpreted on a colloidal basis and more recently this hypothesis has been extended by the thermodynamical studies of Wilsdon and also by the investigations of two of us on an indirect measurement of the vapour pressure of capillary systems. There is evidence that the colloidal portion of the soil can be regarded as possessing a reticulate structure, possibly analogous to that shown by Zsigmondy to exist in silica gels. The pore space in soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1930
1930
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Only in extremely dry soil conditions (desert/arid) will the bulk connectivity of water in the liquid phase break down, which would promote water transport in the vapor phase across the soil even if to a lesser extent when compared with water transport in the liquid phase (Churaev et al, 2000). Water vapor flows in soil due to the soil water content variations are miniscule because the vapor pressure in most soils approaches the saturated vapor pressure at soil water contents greater than the residual water content of the soil (Puri et al, 1925). For example, in sand, the equilibrium humidity is greater than 99.5% even at a suction pressure of 600 MPa (Hillel, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Only in extremely dry soil conditions (desert/arid) will the bulk connectivity of water in the liquid phase break down, which would promote water transport in the vapor phase across the soil even if to a lesser extent when compared with water transport in the liquid phase (Churaev et al, 2000). Water vapor flows in soil due to the soil water content variations are miniscule because the vapor pressure in most soils approaches the saturated vapor pressure at soil water contents greater than the residual water content of the soil (Puri et al, 1925). For example, in sand, the equilibrium humidity is greater than 99.5% even at a suction pressure of 600 MPa (Hillel, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas in the wet range the SWR curve is the expression of capillary forces, in the dry range, adsorption dominates the relationship between water content and the forces that hold this water in its condensed state. Water adsorption onto soils has been studied by different authors [ Puri et al , 1925; Orchiston , 1952; Chiou and Shoup , 1985; Valsaraj and Thibodeaux , 1988; Rhue et al , 1989; Pennell et al , 1992; Amali et al , 1994; Ruiz et al , 1998; Chen et al , 2000a; de Seze et al , 2000] and it has been shown that it can be described by the conventional BET isotherm [ Valsaraj , 1995]. This adsorption isotherm is written here as where is a pseudo‐volumetric water content at monolayer capacity.…”
Section: Soil‐water Retention Modelmentioning
confidence: 99%
“…The absorption isotherms of the various types of solids given by Puri, Crowther, and Keen ( 1925) are instruc-tive from several point of view. These curves show the typical S-shape displayed by many hygroscopic materials, they indicate that if a soil is dried larger amounts of water have to be removed to shift the equilibrium humidity, for instance from 99 to 90 per cent, whereas with further water loss small differences in moisture content cause a rapid drop in humidity.…”
Section: Ment Of Wirewormsmentioning
confidence: 99%